Family Ownership and Firm Performance in Indonesia - ., Juanda; ., Jalaluddin (KnE Social Sciences, 2018)
The purpose of this paper is to investigate the influence of family ownership on the financial performance of firms listed on the Indonesian Stock Exchange from 2008 to 2012. The methodology used is multiple linear regression. The financial performance is measured with return on assets (ROA). The research shows that family ownership does not significantly influence firm performance. This paper is particularly important to the policymakers and shareholders of firms in Indonesia and other developing economies since it provides a comprehensive insight into the family ownership – firm performance relationship and therefore it helps them to formulate the best policies. Keywords: ROA, family ownership, firm performance